SANCTIONS FOR PLAGIARIZERS OF SCIENTIFIC PAPERS FROM THE PERSPECTIVES OF POSITIVE LAW AND ISLAMIC LAW - Amirullah, Muhammad; Maulana, M Luthfillah (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2025)
This study aims to explain and analyze the sanctions for plagiarism in writing scientific papers from the perspective of Islamic law and positive law. The main focus of this study is to understand how Islamic law and positive law view plagiarism and the sanctions that should be applied to the perpetrators. It is hoped that this study can provide better insight into the appropriate sanctions for plagiarism perpetrators, as well as encourage awareness of the importance of academic integrity among students. Thus, this study not only aims to provide solutions to the problem of plagiarism, but also to improve the quality of education and appreciate scientific work in Indonesia. This study uses normative legal research and library research by conducting a review of laws and regulations, books, and fiqh books related to the title of this thesis. The results of this study indicate that in Positive Law, Plagiarism perpetrators can be subject to administrative, academic, or criminal sanctions, depending on the level of error and the impact caused. In Islamic Law, Plagiarism is considered an act of violating copyright and is a form of injustice. Punishment in Islam is ta'zir, which can be in the form of a warning, fine, or other punishment determined by the authorities to provide a deterrent effect to the perpetrator.